Impulsivity predicts illness severity in long-term course of bipolar disorder: A prospective approach. (September 2018) - Rote, Jonas; Dingelstadt, Alice-Mai-Ly; Aigner, Annette; Bauer, Michael; Fiebig, Jana; König, Barbara; Kunze, Johanna; Pfeiffer, Steffi; Pfennig, Andrea; Quinlivan, Esther; Simhandl, Christian; Stamm, Thomas J
Background: Bipolar disorder is a common, severe and chronic mental illness. Despite this, predictors of illness severity remain poorly understood. Impulsivity is reported to be associated with bipolar disorder and aggravating comorbidities. This study therefore sought to examine the predictive value of impulsivity for determining illness severity in euthymic bipolar disorder patients. Methods: Baseline trait impulsivity of 120 bipolar euthymic patients (81 bipolar disorder I [68%], 80 female [67%]) and 51 healthy controls was assessed using Barratt Impulsiveness Scale 11. The impact of impulsivity on illness severity (measured with morbidity index) was prospectively tested in 97 patients with sufficient follow-up data (average observation time: 54.4 weeks), using linear regression analysis. Results: Barratt Impulsiveness Scale 11 total (β = 0.01; p < 0.01) and in particular Barratt Impulsiveness Scale 11 attentional subscale scores (β = 0.04; p < 0.001) predicted illness severity in bipolar disorder, while controlling for other clinical variables. Only age at onset persisted as an additional, but less influential predictor. Barratt Impulsiveness Scale 11 total scores and Barratt Impulsiveness Scale 11 attentional subscale scores were significantly higher in euthymic patients compared to controls. This was not observed for the motor or non-planning subscale scores. Limitations: The average year-long observation time might not be long enough to account for the chronic course of bipolar disorder. Conclusion: Trait impulsivity and particularly attentional impulsivity in euthymic bipolar patients can be strong predictors of illness severity in bipolar disorder. Future studies should explore impulsivity as a risk assessment for morbidity and as a therapeutic target in bipolar disorder patients.